2021
DOI: 10.1093/cercor/bhab153
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Axon Collaterals of Callosal Neurons Form Association Projections from the Primary Somatosensory to Motor Cortex in Mice

Abstract: Association projections from cortical pyramidal neurons connect disparate intrahemispheric cortical areas, which are implicated in higher cortical functions. The underlying developmental processes of these association projections, especially the initial phase before reaching the target areas, remain unknown. To visualize developing axons of individual neurons with association projections in the mouse neocortex, we devised a sparse labeling method that combined in utero electroporation and confocal imaging of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…We have previously shown that, although all commissural axons project laterally through the anterior commissure in dunnarts, the adult brains have medial projections from S1 that project within the gray matter and terminate in the ipsilateral cingulate cortex 12 . A similar population of intracortical medially projecting neurons that are formed postnatally, after the establishment of the corpus callosum (between P2 and P8), has been demonstrated in mice 49 , 50 . This medial ipsilaterally projecting tract in dunnarts is an intriguing candidate that may have contributed physical and/or molecular cues that were adopted during the evolution of the corpus callosum in eutherians, and we therefore used it as an opportunity to compare the timing of medially versus laterally projecting axons between species, despite very different projection targets.…”
Section: Resultsmentioning
confidence: 64%
“…We have previously shown that, although all commissural axons project laterally through the anterior commissure in dunnarts, the adult brains have medial projections from S1 that project within the gray matter and terminate in the ipsilateral cingulate cortex 12 . A similar population of intracortical medially projecting neurons that are formed postnatally, after the establishment of the corpus callosum (between P2 and P8), has been demonstrated in mice 49 , 50 . This medial ipsilaterally projecting tract in dunnarts is an intriguing candidate that may have contributed physical and/or molecular cues that were adopted during the evolution of the corpus callosum in eutherians, and we therefore used it as an opportunity to compare the timing of medially versus laterally projecting axons between species, despite very different projection targets.…”
Section: Resultsmentioning
confidence: 64%